PWE-025 Microscopic colonic inflammation in immune check point inhibitor-induced diarrhoea/colitis. (8th June 2018) - Ibraheim, Hajir; Spain, Lavinia; Samani, Amit; Papa, Sophie; Yousaf, Nadia; Gore, Martin; Larkin, James; Turajlic, Samra; Powell, Nick
Abstract : Background: Immune check point inhibitors (ICPis) have transformed the treatment landscape for several cancers, but at the cost of triggering ICPi-induced colitis which resembles some aspects of IBD. Diagnosis is often made by symptoms, or by identifying endoscopic features of colitis. Little is known about histological findings in the absence of macroscopic disease. Furthermore, first-line management strategies beyond the use of systemic corticosteroids have not been explored. Our aim was to assess the incidence of microscopic inflammation in patients with ICPi-diarrhoea, and report our experience of treating two such patients with beclomethasone diproprionate (Clipper). Methods: Electronic records of patients with advanced melanoma and ICPi- diarrhoea/colitis at the Royal Marsden Hospital (RMH) and Guy's and St Thomas' Hospital (GSTT) between 2011–2016, were retrospectively reviewed. Endoscopic, histological and clinical outcome data was recorded for patients who underwent flexible sigmoidoscopy and had colonic biopsies taken regardless of macroscopic findings. Two symptomatic patients (one treated with anti-PD-1, and another on combination -anti-PD-1/anti-CTLA-4 therapy) with isolated microscopic disease were managed with 5 mg Clipper, once a day, for 4 weeks. Endoscopic, histological and clinical outcomes were recorded 6 weeks after completion of therapy. Results: A total of 63 flexible sigmoidoscopies were performed in 59 patients with ICPi diarrhoea/colitis. Microscopic inflammation with normal macroscopic appearances were recorded in 22% of cases. 6 patients were prescribed anti-CTLA-4, 4 anti-PD-1, and 4 combination therapy. Histological features that were distinct from conventional microscopic colitis were recorded in the majority of patients (10/14), which included acute and chronic inflammation, architectural distortion, crypt abscess formation and neutrophil infiltration. Four patients had changes consistent with conventional microscopic colitis (2 lymphocytic colitis, 2 collagenous colitis). Clipper induced clinical remission within 7 days, and histological remission by week 6 in both patients with ICPi-induced microscopic inflammation. There was no treatment associated adverse events. Conclusion: Microscopic inflammation in the absence of macroscopic features of colitis is a common finding in ICPi-induced diarrhoea, justifying the routine practice of performing colonic biopsies even when endoscopy is normal. Our favourable clinical experience of using Clipper in 2 patients with microscopic inflammation merit further investigation in appropriately controlled clinical trials.